Vulnerable Road Users Overtaking Path Planning on Urban Road considering Individual Driving Styles - Vu, Manh Dung; Aoki, Hirofumi; Dong, Haitao; Nagiri, Sueharu; Nguyen, Thanh Tung; Le, Anh Son; Suzuki, Tatsuya (Smart Systems and Devices, 2022)
In order to reduce the number of traffic accidents related to vulnerable road users (cyclists, pedestrians), recent studies show great interests in developing intelligent technologies for Advanced Driver Assistance Systems. One of the latest functions is navigating the vehicle in a reference trajectory to avoid the possible collision. However, the assistance system may be deactivated due to disagreement of ideal reference path between individuals. In this paper, we proposed the path planning method considering driving styles of drivers for overtaking a moving vulnerable road user on urban road where there is no clear risk of collision. The optimal paths which were generated based on widely studied artificial potential field method are expected to be human-like and generally accepted by drivers. An improved repulsive function was proposed for representing a vulnerable road user walking on the shoulder of the road. The parameters of potential functions for each driving style were identified using avoidance driving data. Then the potential map was created and unique reference paths were calculated with gradient descent method. The proposed method can be a useful integration to Advanced Driver Assistance Systems for gaining driver’s mutual acceptance in approaching and avoiding a moving vulnerable road user.